An Investigation on Chemical and Bacteriological Quality of Seyhan River Water in the Province of Adana, Turkey - Tanir, Ferdi; Sutoluk, Zeynel; Lugal Goksu, M.Z.; Akbaba, Muhsin (Asian Journal of Chemistry, 2016)
This study aims to find out the dimension of water pollution in Seyhan river and make contribution to other studies which may be conducted for the purpose of increasing the water quality. Investigation was conducted from 6 stations on seasonal base in 2001 and 2002. The results of the analysis were presented after being evaluated with variance analysis on SPSS program. The bacteriological pollution in the samples obtained from city stations is attributed to the pollution of phenol, zinc, copper and total phosphor and that there is also bacteriological pollution in the samples obtained from the stations on the way to the shore where the river joins with the sea, which is due to the pollution of nickel, phenol, zinc, copper and lead.